Response-ability in the era of AIDS Building social capital in community care and support - Dageid, Wenche; Duckert, Fanny; Sliep, Yvonne; Akintola, Olagoke (UJ Press, 2014)
The aim of this book is to disseminate the results of research, and to inform, inspire and create a platform for debate between practitioners, academics, researchers, trainers and facilitators interested in addressing community needs in terms of HIV/AIDS and support.